Pengaruh Kepemimpinan Kepala Sekolah, Lingkungan Kerja, Dan Fasilitas Belajar Terhadap Kinerja Guru Dengan Motivasi Kerja Sebagai Variabel Moderasi (Studi Pada SD Negeri Se-Kecamatan Singkep) - Marlina Marlina; Fakhruddin Fakhruddin (CV. Ulil Albab Corp, 2026)
This study aims to analyze the influence of principal leadership, work environment, and learning facilities on teacher performance with work motivation as a moderating variable in public elementary schools in Singkep District. The study used a quantitative approach with survey methods. Data were collected through questionnaires distributed to teachers in public elementary schools. The results indicate that principal leadership, work environment, and learning facilities have a positive and significant effect on teacher performance. Work motivation also strengthens the relationship between these variables and teacher performance. The findings indicate that improving teacher performance requires support from transformational leadership, conducive work environments, adequate learning facilities, and strong work motivation.